The Type of Anesthesia Technique Does Not Have an Impact on 30-Day Mortality in Geriatric Patients Undergoing Lower Extremity Amputation - (:unkn) unknown (INT COLLEGE OF SURGEONS, 2017)
This study aimed to determine the appropriate anesthetic technique for patients who underwent amputation due to peripheral vascular disease. The anesthetic technique to be applied during lower extremity amputations in geriatric patients with limited functional capacity may be important in terms of clinical outcomes and mortality rates. Patients aged older than 65 years who had undergone major lower extremity amputation were retrospectively evaluated. The patients were divided into 2 groups: regional anesthesia (RA) and general anesthesia (GA). Demographic characteristics, comorbidities, medications used, anesthesia technique, the durations of anesthesia and surgery, need for blood transfusion, 30-day mortality, postoperative cardiac and pulmonary complication rates were recorded from the medical records of the patients. Among the 441 patients, 244 had received RA, while 197 had received GA. The average length of stay in the hospital was longer in the GA group (P = 0.001). The use of antiplatelet drugs (P = 0.001) and the number of transfusions were higher (P = 0.045) in the GA group. No significant difference was found between the groups in terms of mortality and postoperative cardiac or pulmonary complication rates. We determined that the anesthesia technique does not have an effect on 30-day mortality and complication rates. The regional anesthesia technique may be preferred in geriatric patients who will undergo major lower extremity amputation because of the shorter hospital stay and theoretical advantages. However, considering the general functional status of patients, the importance of patient-based evaluation should not be forgotten.
Keywords: Amputation; General anesthesia; Geriatric patient; Regional anesthesia; Mortality; Patient care; GENERAL-ANESTHESIA; MORBIDITY; OUTCOMES